The cyclin-dependent kinase inhibitor AT7519 accelerates neutrophil apoptosis in sepsis-related acute respiratory distress syndrome. Issue 2 (24th October 2016) - Dorward, David A; Felton, Jennifer M; Robb, Calum T; Craven, Thomas; Kipari, Tiina; Walsh, Timothy S; Haslett, Christopher; Kefala, Kallirroi; Rossi, Adriano G; Lucas, Christopher D
Abstract : Acute respiratory distress syndrome (ARDS) is a neutrophil-dominant disorder with no effective pharmacological therapies. While the cyclin-dependent kinase inhibitor AT7519 induces neutrophil apoptosis to promote inflammation resolution in preclinical models of lung inflammation, its potential efficacy in ARDS has not been examined. Untreated peripheral blood sepsis-related ARDS neutrophils demonstrated prolonged survival after 20 hours in vitro culture. AT7519 was able to override this phenotype to induce apoptosis in ARDS neutrophils with reduced expression of the pro-survival protein Mcl-1. We demonstrate the first pharmacological compound to induce neutrophil apoptosis in sepsis-related ARDS, highlighting cyclin-dependent kinase inhibitors as potential novel therapeutic agents.